2012
DOI: 10.1111/dom.12006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dual PPAR‐α/γ agonist aleglitazar on glycaemic control and organ protection in the Zucker diabetic fatty rat

Abstract: Aleglitazar strongly improved glycaemic and lipid parameters while protecting key tissues, including the pancreas, kidneys and eyes, against diabetes-associated structural and functional changes in the ZDF rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Investigations on the potential beneficial effects of duel or triple PPAR ligands are emerging. This novel class of PPAR ligands may be able to avoid potential side effects of each single ligand [93] . Phase Ⅱ clinical trials for a dual PPARα/γ agonist, aleglitazar, validate their hypoglycemic and hypolipidemic effects [94] .…”
Section: Regulating Redoxmentioning
confidence: 99%
“…Investigations on the potential beneficial effects of duel or triple PPAR ligands are emerging. This novel class of PPAR ligands may be able to avoid potential side effects of each single ligand [93] . Phase Ⅱ clinical trials for a dual PPARα/γ agonist, aleglitazar, validate their hypoglycemic and hypolipidemic effects [94] .…”
Section: Regulating Redoxmentioning
confidence: 99%
“…Combined PPAR‐α/γ activation with aleglitazar has favourable effects on glucose and lipid profiles, biomarkers of cardiovascular risk and renal function . Aleglitazar's effects are believed to be partly achieved by improvement of β‐cell function . The present phase II trial investigated the potential metabolic effect of aleglitazar on whole‐body and liver insulin sensitivity, β‐cell function and other components of cardiometabolic syndrome, compared with placebo, in patients with type 2 diabetes mellitus (T2DM) inadequately controlled with metformin monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted from cultured cells using TRIzol ® reagent (Invitrogen; Thermo Fisher Scientific, Inc.). Single-stranded complementary (c)DNA was generated from DNaseI-treated RNA samples using Moloney murine leukemiavirus reverse transcriptase and oligo(dT) [12][13][14][15][16][17][18] (Toyobo Life Science, Osaka, Japan). A total of 1 µl cDNA samples were used for conventional PCR amplifications.…”
Section: H-fabp Small Interfering (Si)rna Transfectionmentioning
confidence: 99%
“…PPARα is of interest, as it has the ability to reflect the glucose-lowering and lipid-modifying properties of H-FABP knockdown (18). Substantial evidence has demonstrated that PPAR-α agonists have direct effects on several critical pathways contributing to the development and progression of diabetic kidney disease, and in diabetic PPAR-α-knockout mice, diabetic nephropathy is more severe than in wild-type mice, as reviewed by Thomas et al (19).…”
Section: Si-h-fabp Reduces Pa-induced Oxidative Stress In Podocytesmentioning
confidence: 99%